Corrigendum - Agrivita Agrivita (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2019)
Corrigendum to “Physiological Response and Photosynthate Distribution of West Indian Arrowroot at Different Altitudes” [AGRIVITA Journal of Agricultural Science, 41(1), 117-128]